THE FACTORS INFLUENCING PURCHASE INTENTION AMONG CONSUMERS OF SKINTIFIC PRODUCTS - Natalia, Angel; Utama, Louis (International Journal of Application on Economics and Business, 2025)
This study aims to examine the influence of firm-created content and user-generated content on purchase intention through brand passion among Skintific product consumers. The sample in this study consists of 160 respondents selected using a purposive sampling technique, with the criteria of being at least 17 years old, having used Skintific products, and having seen the product content on TikTok. Data was collected through an online questionnaire distributed via social media and processed using statistical analysis with the Structural Equation Modeling (SEM) approach. The results show that both firm-created content and user-generated content have a positive and significant effect on brand passion. Furthermore, brand passion has been proven to have a significant impact on purchase intention. These findings indicate that content strategies, whether from companies or users, play an essential role in enhancing consumers' emotional engagement with the brand and fostering their purchase intention for Skintific products.